AN ANALYSIS OF THE FORMATION OF AN INTERTEXTUAL UNITY OF TEXTS IN THE INSTRUMENTAL ARTWORK ENTITLED MATSURI BY KITARO - Napitupulu, Lilis Handayani (English Language Teaching Prima Journal (ELT), 2024)
This study seeks to identify the intertextual elements in Matsuri and explore how they contribute to a cohesive understanding of the piece, focusing on its relationship to Japanese culture and spirituality. A descriptive qualitative approach was employed, using textual analysis to examine Matsuri as both a verbal and visual text. Data was gathered from library sources, including written texts and media related to Kojiki, the ancient Japanese text that inspired the album's themes. Matsuri incorporates both verbal and visual texts. Verbal elements include references to Kojiki and titles in the album, while visual elements involve traditional Japanese instruments like the Taiko drum, which connect the music to Japanese rituals and festivals. This blend of traditional and modern influences highlights cultural continuity within Japan’s modern identity. The intertextuality in Matsuri reveals its dual role as a reflection of Japanese cultural heritage and as a medium for personal and communal identity formation. The persistence of traditional practices, even as they evolve with modernization, underscores the enduring significance of rituals like Matsuri in Japanese society.